2022
DOI: 10.3390/plants11091238
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Position and Markers Associated with the Hull-Less Seed Trait in Pumpkin

Abstract: Pumpkin (Cucurbita pepo) seeds are nutritious and valued as a source of vegetable oil, protein, healthy fatty acids, and minerals. Pumpkin seeds that are naturally devoid of the seedcoat (hull-less) are preferred by the industry as they eliminate the need for de-hulling prior to use. A single recessive gene, designated as n or h, controls the hull-less seed trait in pumpkin. Visual selection for the trait is easy, however, it is resource intensive when applied to large breeding populations. High throughput gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
3
6
1
Order By: Relevance
“…In support to this, our recently published manuscript 22 identified a candidate genomic region linked to hull-less seed trait ranging from 1.80 to 3.86 Mb on chromosome 12 of C. pepo genome and also reported a linked KASP marker. Similar results are also reported by two other recently published studies in C. pepo 23 , 24 . Further, BLASTn results of polymorphic SSR markers with C. pepo (Zucchini) genome revealed that only CMTp182 had the significant hits on chromosome 12 in between the identified candidate genomic region (CMTp182 Forward: 2220598–2220615 and CMTp182 Reverse: 2220732–2220713).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In support to this, our recently published manuscript 22 identified a candidate genomic region linked to hull-less seed trait ranging from 1.80 to 3.86 Mb on chromosome 12 of C. pepo genome and also reported a linked KASP marker. Similar results are also reported by two other recently published studies in C. pepo 23 , 24 . Further, BLASTn results of polymorphic SSR markers with C. pepo (Zucchini) genome revealed that only CMTp182 had the significant hits on chromosome 12 in between the identified candidate genomic region (CMTp182 Forward: 2220598–2220615 and CMTp182 Reverse: 2220732–2220713).…”
Section: Discussionsupporting
confidence: 93%
“…These results are similar to the previous reports in C. pepo by Stuart 40 , Zraidi et al 41 and Lelley et al 3 . More recently, along with monogenic recessive inheritance, hull-less seed trait has been mapped to chromosome 12 of C. pepo genome with 'NST1' (Cp4.1Lg12g04350) as the putative candidate gene [22][23][24] . However, segregation distortion observed in Family IV, might be due to incomplete representation of whole F 2 population in chi square analysis.…”
Section: Total Number Of F 2 Seeds Sownmentioning
confidence: 99%
“…A KASP assay viz ., Cp_3430407 can be utilized for MAS with 93.33% accuracy in hull-less germplasm of C. pepo . The physical positions of this KASP assay are also close to recently identified SNP markers (Ch12_3412046 and Ch12_3417142) reported by Meru et al ( 2022 ).…”
Section: Discussionsupporting
confidence: 86%
“…A KASP assay viz., Cp_3430407 can be utilized for MAS with 93.33% accuracy in hull-less germplasm of C. pepo. The physical positions of this KASP assay are also close to recently identified SNP markers (Ch12_3412046 and Ch12_3417142) reported by Meru et al (2022). The molecular mechanism of cell wall lignification has been well-studied in Arabidopsis, and over the years, this knowledge has been translated to understand the lignification mechanism in crops (Wang and Dixon, 2012;Barros et al, 2015).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation